The Study on the Multi-Factor Influences on Hydraulic Fracturing Expansion Based on Numerical Simulation - Zhou, Zhiyu; Guo, Hongyong (Scientific Journal of Technology, 2025)
With the development of unconventional oil and gas resources, hydraulic fracturing technology has played a crucial role in the exploitation of shale gas, tight oil, and other reservoirs. The expansion morphology of fractures significantly impacts the fracturing effectiveness, and the geometric characteristics of the fractures are influenced by rock mechanical parameters and geological conditions. This study systematically investigates the effects of Young's modulus, Poisson's ratio, brittleness index, and horizontal stress difference on the fracture propagation path, width, and length in hydraulic fracturing, using numerical simulation methods. The simulation results indicate that Young's modulus is closely related to fracture stiffness, with higher values leading to reduced fracture width and increased length. Poisson's ratio affects the deformation behavior of fractures, with larger Poisson's ratios causing more uniform fracture deformation. When the brittleness index is higher, fractures tend to adopt a more elongated shape. The horizontal stress difference influences the directional propagation of fractures, with larger stress differences resulting in more linear fracture shapes. This study provides theoretical support for fracture design and fracturing parameter optimization in hydraulic fracturing operations, aiming to improve fracturing efficiency and optimize oil and gas recovery.